PENGARUH PENERAPAN SISTEM E-FILING DAN KESADARAN WAJIB PAJAK TERHADAP TINGKAT KEPATUHAN WAJIB PAJAK ORANG PRIBADI DI KOTA AMBON - Rehatta, Valensia; Engko, Cecilia; Kriswantini, Dwi (Jurnal Akuntansi, 2021)
The purpose of this study was to determine: (1) The effect of the application of the e-filing system on the level of individual taxpayer compliance in Ambon City, (2) the effect of taxpayer awareness on the level of individual taxpayer compliance in Ambon City.The population on this study is taxpayers registered as user e-filing taxpayers in KPP Pratama Ambon. The number of samples in this study is 70 respondents. Data in this study were obtained primarily through a questionnaire (questionnaire). The sampling technique used Purposive sampling method. The questionnaire was tested for validity and reliability testing before the study. The classical assumption test used is the normality test, heteroscedasticity test and multicollinearity test. The hypothesis test used is multiple linear regression analysis. The results of this study indicate that The application of the e-filing system and Taxpayer Awareness has a positive and significant effect on individual taxpayer compliance in Ambon City. This is indicated by the coefficient of determination 0.641, which means that the application of the e-filing system and Taxpayer Awareness affects taxpayer compliance by 64.1%